Hubungan Individual Stressor dengan Stres Kerja pada Pekerja Kantor Bagian Pab Rehandling di Sektor Pertambangan - Karina Putri Maharani; Ida Umarul Mufidah; Nico Linggi Pongmasangka (Inovasi Kesehatan Global, 2024)
PAB Rehandling office workers in the mining sector, these stressors have a greater impact due to the dynamic and often dangerous nature of the work. Office workers responsible for transporting materials and processing associated paperwork are often under pressure to meet strict production targets. This pressure can be exacerbated by a work environment fraught with safety risks, leading to increased levels of anxiety and stress. To determine the correlations of individual stressors (age, gender, and tenure) with occupational stress. Using quantitative methods using a cross sectional design. The sampling technique used was total sampling so that the sample in this study was office workers in the PAB Rehandling section in the Mining Sector, totaling 56 respondents. Data analysis using Spearman test for ordinal data types (age and tenure) and Chi Square test for nominal data types (gender). The study showed that there was a correlation between age with a p-value of 0.032, there was no correlation between gender with a p-value of 0.873, there was a correlation between tenure with a p-value of 0.000. To minimize the high level of stress in PAB Rehandling office workers, it is possible to implement a program to implement stress management in the workplace.